Disfuncionalidad familiar y su incidencia en la conducta y el bajo rendimiento de los estudiantes del octavo año del colegio Dra. Matilde Hidalgo de Procel de la ciudad de Machala, año lectivo 2014- 2015. - Zenteno Fajardo, Fanny Natali (2015)
The research analyzes the current problems that our country has a high rate of family dysfunction, so our object of study focused on family dysfunction and its impact on behavior and low performance students who attend school Dra. Matilde Hidalgo, year 2014-2015, determining how family dysfunction in behavior and poor school performance among students is related.